2009
DOI: 10.1016/j.physbeh.2009.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences and reproductive hormone influences on human odor perception

Abstract: The question of whether men and women differ in their ability to smell has been the topic of scientific investigation for over a hundred years. Although conflicting findings abound, most studies suggest that, for at least some odorants, women outperform men on tests of odor detection, identification, discrimination, and memory. Most functional imaging and electrophysiological studies similarly imply that, when sex differences are present, they favor women. In this review we examine what is known about sex-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
309
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 402 publications
(346 citation statements)
references
References 152 publications
(156 reference statements)
32
309
2
3
Order By: Relevance
“…Reasons for gender differences regarding taste changes are currently unknown. In general, there is evidence that women have a greater taste and smell sensitivity than men (25,26). Therefore, female cancer patients may be more prone to changes in taste function than men.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for gender differences regarding taste changes are currently unknown. In general, there is evidence that women have a greater taste and smell sensitivity than men (25,26). Therefore, female cancer patients may be more prone to changes in taste function than men.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, genetic chemoreceptors that modulate taste perception change along life and when in contact with several stimuli, chronic conditions and environmental influences. Correa et al [42] observed that children up to 8 years of age showed a larger number of fungiform gustatory papillae than adults (p = 0.025) [42,43]. The National Institutes of Health (NIH) offers a toolset for the assessment of bitterness perception.…”
Section: Bitterness Perception and Agementioning
confidence: 99%
“…The as sociation between olfaction and anxiety is unstudied in pa tients with schizophrenia, but SIT deficits have been found in patients with obsessive-compulsive disorder (OCD) 22 and posttraumatic stress disorder (PTSD). 23 In the present study, we assessed odour sensitivity and SIT using the Smell Threshold Test 24 and the University of Pennsyl vania Smell Identification Test (UPSIT), 25 respectively, and fo cused on quantifiable aspects of anhedonia and anxiety using the Chapman Social and Physical Anhedonia 26 and Liebowitz Social Anxiety (LSAS) 27 scales. Our 3 aims were to compare the presence of anhedonia and anxiety between patients with schizophrenia and healthy controls, to investigate the impact of anhedonia and anxiety on social function so as to shed light on whether anhedonia and anxiety are single or dual pathological domains within schizophrenia influencing social function, and to use olfactory function to explore if the biological underpin nings of anxiety and anhedonia were shared or distinct in pa tients with chronic schizophrenia.…”
Section: J Psychiatry Neurosci 2015;40(6)mentioning
confidence: 99%